Los proyectos de ley en torno a las tarjetas electrónicas - Romero Pérez, Jorge Enrique (2018)
This paper presents and comments on the topic by relating electronic cards with the crime of usury, through the analysis of three bills submitted to the Congress with regard to:i) Law regulating the market of credit and debit cards, 2008ii) Law for the protection of the rights of users of credit and debit cards, 2010; and,iii) Law against usury, 2017.    Additionally, this article introduces and comments on several documents prepared by the Ministry of Economy, Industry and Trade, which are characteristic of this field of analysis.